Effectiveness and recovery action of a perturbation balance test – a comparison of single-leg and bipedal stances. Issue 10 (27th July 2018) - Petró, Bálint; T Nagy, Judit; Kiss, Rita M
Abstract: Dynamic balancing abilities can be assessed with perturbation tests. The present study examined the effectiveness of balancing (damping ratio) and the recovery action (directional ratio) in bipedal and dominant single-leg stance in the young population. Twenty-four healthy young adult participants completed unidirectional lateral perturbations successfully using a Posturomed© platform (Haider Bioswing, Germany). Single-leg stances had similar damping scores ( p = 0.551) to and lower directional ratio values ( p = 0.002) than bipedal recoveries. This shows that different recovery actions can achieve similar effectiveness in the two stances. A test evaluation methodology that simultaneously utilises performance and motion characteristic parameters was demonstrated.